Expression analysis using reverse transcription quantitative Real-Time PCR (RT-qPCR) suggests different strategies in Parageobacillus caldoxylosilyticus ER4B under exposure to cold shock - Ching, Xin Jie; Noor Hydayaty Md Yusuf,; Nazalan Najimudin,; Cheah, Yoke Kqueen; Michael, Clemente Wong Vui Ling (Universiti Kebangsaan Malaysia, 2022)
Microorganisms have acquired both common and unique abilities to withstand cold stress on Earth. Many studies on bacterial cold shock have been conducted, however, the majority of the studies were focused on mesophiles and psychrophiles. To date, limited information is available on the response of thermophilic bacteria to cold stress and therefore, it is not known how thermophilic bacteria would respond to different cold shocks. To address this question, the cold shock responses of a thermophilic Parageobacillus caldoxylosilyticus ER4B which has an optimal growth temperature at 64 °C were determined using Real-Time PCR (RT-qPCR). When the bacterium was exposed to mild cold shock at 54 °C, the expressions of gene encoding for pyruvate kinase and acetolactate synthase were significantly upregulated, suggesting that more pyruvate molecules were produced to synthesize branched-chain amino acids that could alter the fatty acid profile on the cell membrane. Accumulation of pyruvate in the bacterium could also help to scavenge cold-induced reactive oxygen species (ROS). Meanwhile, exposing the bacterium to extreme cold shock at 10 °C resulted in significant upregulation of genes encoding for γ-glutamylcyclotransferase, cold shock protein B and competence protein ComEA. An increase in these enzymes expression indicated more extreme measures including apoptosis and transformation were adopted during extreme cold shock.